Multidisciplinary guidelines for the management of paediatric tracheostomy emergencies. (31st July 2018) - Doherty, C.; Neal, R.; English, C.; Cooke, J.; Atkinson, D.; Bates, L.; Moore, J.; Monks, S.; Bowler, M.; Bruce, I. A.; Bateman, N.; Wyatt, M.; et al.
Summary: Temporary and permanent tracheostomies are required in children to manage actual or anticipated long‐term ventilatory support, to aid secretion management or to manage fixed upper airway obstruction. Tracheostomies may be required from the first few moments of life, with the majority performed in children < 4 years of age. Although similarities with adult tracheostomies are apparent, there are key differences when managing the routine and emergency care of children with tracheostomies. The National Tracheostomy Safety Project identified the need for structured guidelines to aid multidisciplinary clinical decision making during paediatric tracheostomy emergencies. These guidelines describe the development of a bespoke emergency management algorithm and supporting resources. Our aim is to reduce the frequency, nature and severity of paediatric tracheostomy emergencies through preparation and education of staff, parents, carers and patients.